1999
DOI: 10.1021/bi9818570
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode EPR Study of New Signals from the S3-State of Oxygen-Evolving Complex in Photosystem II

Abstract: The light-induced new EPR signals at g = 12 and 8 were observed in photosystem II (PS II) membranes by parallel polarization EPR. The signals were generated after two flashes of illumination at room temperature, and the signal intensity had four flashes period oscillation, indicating that the signal origin could be ascribed to the S3-state. Successful simulations were obtained assuming S = 1 spin for the values of the zero-field parameters, D = +/-0.435 +/- 0. 005 cm-1 and E/D = -0.317 +/- 0.002. Orientation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 28 publications
(45 reference statements)
11
97
1
1
Order By: Relevance
“…Parallel-mode EPR studies by Matsukawa and co-workers have shown the presence of EPR resonances at g = 12 and 8 that are best simulated by an S = 1 excited-state spin species in the S 3 state. 87 The authors rationalize these results as arising from a coupling between the S = ½ complex, characterized by the MLS EPR signal, interacting with an S = ½ radical produced during the S 3 transition that leads to the disappearance of the MLS and generation of an integer spin state.…”
Section: Implication To the Mechanism Of Water Oxidationmentioning
confidence: 93%
“…Parallel-mode EPR studies by Matsukawa and co-workers have shown the presence of EPR resonances at g = 12 and 8 that are best simulated by an S = 1 excited-state spin species in the S 3 state. 87 The authors rationalize these results as arising from a coupling between the S = ½ complex, characterized by the MLS EPR signal, interacting with an S = ½ radical produced during the S 3 transition that leads to the disappearance of the MLS and generation of an integer spin state.…”
Section: Implication To the Mechanism Of Water Oxidationmentioning
confidence: 93%
“…The EPR spectrum of S 3 was first reported by Matsukawa, et al, who also reported a phenomenological simulation. [236] 6.6. …”
Section: Angewandte Chemiementioning
confidence: 99%
“…A variety of techniques have been applied, including electron paramagnetic resonance (EPR) spectroscopy Boussac et al 1989;Britt et al 2004;Britt et al 2000;Kulik et al 2005a;Kulik et al 2005b;Kulik et al 2005c;Matsukawa et al 1999;Messinger et al 1997a;Messinger et al 1997b;Miller & Brudvig 1991;Mino & Kawamori 2001;Nugent et al 1997;Peloquin & Britt 2001;Peloquin et al 1998;Peloquin et al 2000;Poluektov et al 2005;Razeghifard & Pace 1999), X-ray absorption spectroscopy (XAS) (Dau et al 2001;Dau et al 2003;Dau et al 2004;Grabolle et al 2006;Hasegawa et al 1999;Haumann et al 2005a;Haumann et al 2005b;Iuzzolino et al 1998;Liang et al 2000;Mishra et al 2007;Riggs-Gelasco et al 1996;Robblee et al 2002;Sauer & Yachandra 2004;Sauer et al 2005;Stemmler et al 1997;Yachandra 2002;Yachandra et al 1986;Yachandra et al 1987;Yano et al 2006;Yano et al 2005b), Fourier transform infrared (FTIR) spectroscopy (Chu et al 2004;Debus et al 2005;…”
Section: Structure and Mechanism Of The Oecmentioning
confidence: 99%